The role of transformational leadership in promoting social responsibility (An applied study on the Directorate of Health Affairs in Aseer) - Alkhudran, Abdullah Mubarak Said (Journal of Economic, Administrative and Legal Sciences, 2023)
The current study aims to identify the dimensions of transformational leadership represented by (ideal influence, intellectual stimulation, inspirational stimulation, and individual consideration) on the social responsibility among employees in Directorate of Health Affairs at Assir. The field study relied on the analytical descriptive approach by designing and distributing questionnaires to a sample of employees in Directorate of Health Affairs at Assir in order to find out the opinion of the study sample on knowing the role of transformational leadership in enhancing the social responsibility of employees in Directorate of Health Affairs at Assir. The questionnaire included two main axes: transformational leadership and social responsibility. The results also showed a statistically significant relationship between the dimensions of transformational leadership and the level of social responsibility of employees in Directorate of Health Affairs at Asir. The study concluded with many recommendations, the most important of which are: to conduct more studies and field research in public sector organizations on the concept of transformational leadership, and the possibility of benefiting from it by studying other variables such as engineering, administrative creativity, and organizational loyalty.
Keywords: transformational leadership; social responsibility; in Directorate of Health Affairs at Assir